2021
DOI: 10.1002/spy2.147
|View full text |Cite
|
Sign up to set email alerts
|

Introduced a new method for enhancement of intrusion detection with random forest and PSO algorithm

Abstract: As computer networks expand, attacks and intrusions into these networks have increased. In addition to firewalls and other intrusion prevention equipment, other systems, such as IDS (Metrics), are designed to provide enhanced security in computer systems, including the purpose of monitoring intrusive and intrusive activities. Intrusive allocation system can be considered effective if the high intrusion rate is slightly misleading, and in this article a new way to classify it is abnormal (infiltration) in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Specifically, various Machine Learning (ML) and Deep Learning (DL) models have been developed to classify network traffic data in IoT networks. These models learn the discriminating features of benign traffic and malicious traffic using different architectures such as Random Forest (RF) [ 18 ], Support Vector Machine (SVM) [ 19 ], Deep Neural Network (DNN) [ 20 ], Recurrent Neural Network (RNN) [ 21 ], Long Short-Term Memory (LSTM) [ 22 ] and Gated Recurrent Unit (GRU) [ 23 ]. For an in-depth understanding, comprehensive reviews and surveys on the application of ML and DL in intrusion detection are presented in [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, various Machine Learning (ML) and Deep Learning (DL) models have been developed to classify network traffic data in IoT networks. These models learn the discriminating features of benign traffic and malicious traffic using different architectures such as Random Forest (RF) [ 18 ], Support Vector Machine (SVM) [ 19 ], Deep Neural Network (DNN) [ 20 ], Recurrent Neural Network (RNN) [ 21 ], Long Short-Term Memory (LSTM) [ 22 ] and Gated Recurrent Unit (GRU) [ 23 ]. For an in-depth understanding, comprehensive reviews and surveys on the application of ML and DL in intrusion detection are presented in [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the proposed algorithm resulted in significant improvement in the network intrusion detection by 4 to 6% and decreased the false alarm rate by 5–1% from the same models’ corresponding values without pretrains in similar datasets. In [ 20 ], a new method has been introduced for enhancing intrusion detection performance. With increasing network attacks and intrusions in computer networks, the importance of developing security policies, documenting existing threats, and preventing individuals from violating security policies to secure information was identified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bagging follows "voting" and "regression averaging" methods for solving the classification problems. Random forest (RF) is an example of bagging that is widely used in design of an IDS [52]. e structure of bagging algorithm is very much similar to the structure of general ensemble learning and has been shown in Figure 1.…”
Section: Baggingmentioning
confidence: 99%